Changing school start times: Impact on extracurricular activities and employment - Meltzer, Lisa J.; Plog, Amy E.; Wahlstrom, Kyla L.; McNally, Janise (Frontiers in Sleep, 2022)
Sufficient sleep duration is associated with student health and well-being, but early secondary school start times limit students’ sleep opportunity. Despite recommendations that all middle and high schools adopt a healthy school start time policy, one barrier to policy implementation is concerns about the impact on student participation in activities and employment. This study examined student extracurricular activity participation and employment before and after the implementation of healthy secondary school start times. Approximately 24,000 students/year (grades 3-11) completed three annual surveys (pre-change, post-change, follow-up) measuring sleep-wake patterns, extracurricular activity participation, and employment. Following the implementation of an earlier school start time, before-school activity participation decreased for elementary school students, but after-school participation was similar across years. Following the implementation of later school start times, there was a small decrease in after-school activity participation for middle and high school students (~3-4%). Equally important, middle and high school students reported significantly increased sleep duration with later start times, regardless of participation in before- or after-school activities and employment. Study findings support the recommendation for healthy school start time policies.